Ensino médio: estudo bibliométrico da produção científica na plataforma EDUC@ (1976-2021) - Franzo, Yago Caue dos Santos (2024)
The theme of this Master's thesis is High School in Brazil. The investigation posed the following research question: How is the Brazilian scientific production on High School configured in a database of scientific articles in the field of Education? To answer this question, the general objective was set to analyze the scientific production on the investigated theme available on the Educ@ platform of the Fundação Carlos Chagas, which consists of a collection of scientific journals in the field of Education. The research is characterized as exploratory and descriptive of a quantitative-qualitative nature, conducted through bibliometric approach methodologies and content analysis. The research corpus was composed of articles (n=649) published between 1976 and 2021 available in Educ@. The methodological procedures involved the following steps: establishment of the research's theoretical framework; selection of the data source; definition of search expressions in the database; data collection and recording in a research database; definition of the research's quantitative categories based on the bibliometric approach (profile of articles and journals, profile of authors, profile of authorship); and qualitative categories based on content analysis. Among the main results obtained, it stands out that the articles were published between 1976 and 2021 in 56 different journals, with the majority of titles classified in the highest strata (A1-A4) of the Qualis/Capes list; there were a total of 1,305 authors, of which the majority (61.8%) are women and the rest (41.2%) are men; co-authorships prevailed (67.2%) and individual articles (n=213) represented 32.8% of the total; the most frequent type of research was applied study (97.5%) with the remainder (2.5%) being theoretical studies. The content analysis of the articles allowed the categorization of the articles into 16 thematic categories, with the most frequent being 'school content and teacher training' (n=257) and adolescents (n=70). The following research designs were also identified: case studies (n=336); documentary (n=157); bibliographic (n=81), bibliographic-documental (n=50), field study or ethnographic research (n=8), and surveys (n=17). In conclusion, by extensively exploring the Brazilian scientific production on High School, the study not only revealed the evolution and predominant trends of this theme but also provided valuable insights into how legal frameworks influence educational formation in Brazil, highlighting the need for continuous revisions and updates to meet the contemporary and future demands of Brazilian society.